2007
DOI: 10.1158/1078-0432.ccr-06-1785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of CD99 Down-Regulation in Gastric Adenocarcinoma

Abstract: Purpose: CD99 is a cell adhesion molecule associated with human tumors. The aim of the present study was to characterize its role in the development and progression of human gastric adenocarcinoma. Experimental Design: The expression of CD99 was investigated in 283 gastric adenocarcinomas and related lesions and 9 gastric carcinoma cell lines.We also analyzed the methylation status of CD99 gene by using methylation-specific PCR and examined loss of heterozygosity (LOH) of this gene locus by using an intragenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
(24 reference statements)
1
28
0
1
Order By: Relevance
“…This finding further underscore the non-specific diagnostic nature of CD99 as reported in several tumor studies and the collective use of complementary markers [1,4,28,29,30]. However, the recent finding of the role of CD99 in the biological evaluation of certain tumors indicates that further studies are needed [31]. The keratin expression in the rhabdomyosarcoma case was negated by the positive detection of multiple skeletal muscle markers [30,32].…”
Section: Discussionmentioning
confidence: 82%
“…This finding further underscore the non-specific diagnostic nature of CD99 as reported in several tumor studies and the collective use of complementary markers [1,4,28,29,30]. However, the recent finding of the role of CD99 in the biological evaluation of certain tumors indicates that further studies are needed [31]. The keratin expression in the rhabdomyosarcoma case was negated by the positive detection of multiple skeletal muscle markers [30,32].…”
Section: Discussionmentioning
confidence: 82%
“…The immunoreactivity for CD99 in Merkel cell carcinoma should be taken into consideration when diVerential diagnosis with other small round blue cell tumors is considered (Sur et al 2007). Lee et al (2007) reported that the expression of CD99 was signiWcantly decreased in the gastric carcinoma and intestinal metaplasia samples compared with normal gastric epithelial. However, so far CD99 expression status in TCC has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Increased or decreased expression of CD99 has been suggested to act as a marker of various kinds of tumors, including Ewing's sarcoma/primitive neuroectodermal tumors (Fong et al 2008), anaplastic large cell lymphoma (Buxton et al 2009), lymphoblastic lymphoma/leukemia (Kang and Dunphy 2006), rhabdomyosarcoma (Folpe et al 2002;Euscher et al 2008), ovarian tumors (Choi et al 2000), and stomach cancer Lee et al 2007). However, the clinical implication of CD99 in epithelial tumors including transitional cell carcinoma of urinary bladder has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…CD9 is a cell surface protein that has been implicated in a number of cellular processes including cutaneous wound healing 23 ; CD9 was down-regulated in migrating epidermis, and re-elevated to basal level when re-epithelialization was completed, supporting that low level of CD9 is required for normal wound healing 23 . Although its function is not fully understood, CD99 is thought to be involved in a number of cellular events such as cell-cell adhesion and maintenance of cellular morphology, and altered expression levels of CD99 have been found in several types of cancer 24 . We found that CD99 was decreased by 45% (i.e., ratio of treated/untreated cells being 0.55) as a result of NNN exposure.…”
Section: Resultsmentioning
confidence: 99%